2013
DOI: 10.14335/ijsfp.v1i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Focused Brief Therapy in Combination With Fantasy and Creative Language in Working With Children: A Brief Report

Abstract: The main purpose of this study was to describe the application of a model of solution-focused brief therapy (SFBT) integrated with the ideas of storytelling and creative language used in the psychological support service in an Italian school setting. The young clients described their changes and thoughts about the treatment using a self-report questionnaire. There were 32 young clients and the mean age was 13 years old. The data collected show promising first results and the interventions were appreciated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The research methods used are mostly qualitative studies. In terms of research findings, most researchers reported that the use of proverbs in the counseling process made a positive contribution to client change (Ariantini et al, 2019;Ciuffardi et al, 2013;Disassa & Into, 2020;Liu et al, 2012;McRobie & Agee, 2017;Owu-Ewie, 2019;Rahill et al, 2011;Zubaidah, 2019).Second, we find that proverbs and metaphors are two things that cannot be separated in the social reality of society because they are both cultural products. A proverbs in a psychosocial framework reflect the normative aspects of how people think and behave in social situations.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The research methods used are mostly qualitative studies. In terms of research findings, most researchers reported that the use of proverbs in the counseling process made a positive contribution to client change (Ariantini et al, 2019;Ciuffardi et al, 2013;Disassa & Into, 2020;Liu et al, 2012;McRobie & Agee, 2017;Owu-Ewie, 2019;Rahill et al, 2011;Zubaidah, 2019).Second, we find that proverbs and metaphors are two things that cannot be separated in the social reality of society because they are both cultural products. A proverbs in a psychosocial framework reflect the normative aspects of how people think and behave in social situations.…”
Section: Discussionmentioning
confidence: 58%
“…In relation to the topic of metaphors in counseling, we found 5 conceptual review literatures that explain theoretically about the use of metaphors in counseling as a therapeutic change technique (Ahammed, 2010;Genuchi et al, 2016;Tay, 2012;Tay, 2014;Wagener, 2017;Zatloukal et al, 2019). In addition, we also find 8 empirical research literature as evidence that the use of metaphorical techniques has an important role for counselors and is effective in changing clients' thoughts, emotions and behavior (Ciuffardi et al, 2013;Gelo & Mergenthaler, 2012;Komasi et al, 2017;Mashar & Nurihsan, 2017;Rahman, 2015;Robert & Kelly, 2010;Rahill et al, 2011;Shoushtari, 2015). Based on the results of the analysis of the literature, we summarize the metaphor technique into four steps; (1) planning metaphors, (2) delivering metaphors, (3) exploring meanings and new insights, (4) actualizing the benefits of metaphors in real life.…”
Section: Review Proverbs As a Metaphor In Counselingmentioning
confidence: 85%
See 2 more Smart Citations
“…The technique of exaggeration intensifies the discussion theme in a therapeutic process in order to draw out the creative and imaginative potential of the client (Dolliver 1991, Ciuffardi, Scavelli, andLeonardi 2013). In the Sūtra, the chapter "Inconceivable" uses this technique frequently.…”
Section: Exaggeratingmentioning
confidence: 99%